Efektivitas Program Kalimasada Melalui Pelayanan Sayang Warga di Kelurahan Gebang Putih Kota Surabaya - Aditya Saputra, Septian; Rining Nawangsari, Ertien (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The aim of the Kalimasada Program is to increase public awareness regarding the importance of population administration. This program makes it easier to administer population administration services. This research aims to measure the effectiveness of the Kalimasada Program which is implemented through the Citizen Compassion Service in Gebang Putih Subdistrict, Surabaya City. The research method involves qualitative descriptive data analysis. The results of the research show that 1.) The success of the Kalimasada Program has been running quite well, and the community is quite enthusiastic about taking care of the population registration documents that they don't yet have because they don't have to come all the way directly to the Surabaya City Population and Civil Registration Office. 2.) The success of the Kalimasada Program targets has not been on target. , people who are elderly or who don't understand technology don't know what the Kalimasada Program itself is, making it difficult for them to take care of the population administration documents they need. 3.) Satisfaction with the Kalimasada Program can be said to be quite satisfied because people are really helped in taking care of population registration documents without having to come to the Dispendukcapil Office with very easy procedures, although people who are elderly and who don't understand technology have a little difficulty in understanding the Kalimasada Program.4. ) The output produced by the Kalimasada Program is greater than the input provided, even though the Surabaya City Population and Civil Registration Department has to prepare inputs such as various supporting facilities for the Kalimasada Program, it can produce greater output, namely fast, easy, and time-efficient services. 5.) Program Kalimasada has been quite successful in achieving its goals. This can also be seen from the number of people who take care of population administration which increases every year compared to before the Kalimasada Program was launched. The conclusion is that the effectiveness of the Kalimasada Program is quite effective in making a positive contribution to the community of Gebang Putih Subdistrict, Surabaya City. The community is quite helped in processing the population registration documents without having to come to the Surabaya City Population and Civil Registration Department.